Influence Of Profitability, Company Size And Sales Growth Tax Avoidance Against - Yulia Maelani; Lisna Lisnawati; Fanji Farman (Journal of Business, Accounting and Finance, 2021)
Tax avoidance is an effort to minimize the tax burden by utilizing the legal loopholes of law provisions of the taxation. Tax avoidance proxies with the Cash Effective Tax Rate (CETR). This study aims to determine the effect of profitability, company size and sales growth on tax avoidance on property and real estate subsector companies listed on the Indonesia Stock Exchange. The research method used in this research is descriptive quantitative. The population in this study is a property and real estate subsector company listed on the Indonesia Stock Exchange with a sample of research selected based on purposive sampling of 23 companies. The data collected is secondary data. The data analysis method used is multiple linear analysis. The results showed that profitability, company size, and sales growth simultaneously influenced on tax avoidance. Partially, profitability affects tax avoidance. The size of the company affects tax avoidance. Sales growth has no effect on tax avoidance